(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Proniosomes are solid colloidal particles which may be hydrated immediately before use to yield aqueous niosomes dispersions similar to those produced by more cumbersome conventional methods. The proniosomes minimize the problems associated with niosomes in terms of its physical stability such as aggregation, fusion and leaking. They also offer an additional convenience in transportation, distribution, storage, and dosing. The proniosomes derived niosomes are better than conventional niosomes in terms of their morphology, particle size, particle size distribution, and drug release. A slurry method was commonly used to produce proniosomes using maltodextrin as carrier. The time required to produce proniosomes by this simple method is independent of the ratio of surfactant solution to carrier material and appears to be a scalable process. The encapsulation efficiency of proniosomes is depends upon the amount of maltodextrin used in the process. The present review describes the method of preparation, characterization, applications of proniosomes as a potential drug delivery system.